Ultimum Remedium Efforts as an Effort to Ensure Tax Criminal Law - Dharmasetya, Lani (Neolectura, 2023)
This study examines the application of criminal sanctions as ultimum remedium in Indonesian tax law, focusing on how this principle is used as a last resort to enforce the law against tax violations. Through a normative juridical approach, this research analyzes legislation, legal doctrines, and specific cases related to the application of criminal sanctions in the field of taxation. The results show that although the ultimum remedium principle is legally recognized, there are challenges in its implementation, particularly concerning the interpretation of